CryJ-LAMP DNA Vaccines for Japanese Red Cedar Allergy Induce Robust Th1-Type Immune Responses in Murine Model - Yan Su; Michael Connolly; Anthony Marketon; Teri Heiland (Journal of Immunology Research)
Allergies caused by Japanese Red Cedar (JRC) pollen affect up to a third of Japanese people, necessitating development of an effective therapeutic. We utilized the lysosomal targeting property of lysosomal-associated membrane protein-1 (LAMP-1) to make DNA vaccines that encode LAMP-1 and the sequences of immunodominant allergen CryJ1 or CryJ2 from the JRC pollen. This novel strategy is designed to skew the CD4 T cell responses to the target allergens towards a nonallergenic Th1 response. CryJ1-LAMP and CryJ2-LAMP were administrated to BALB/c mice and antigen-specific Th1-type IgG2a and Th2-type IgG1 antibodies, as well as IgE antibodies, were assayed longitudinally. We also isolated different T cell populations from immunized mice and adoptively transferred them into naïve mice followed by CryJ1/CryJ2 protein boosts. We demonstrated that CryJ-LAMP immunized mice produce high levels of IFN-γ and anti-CryJ1 or anti-CryJ2 IgG2a antibodies and low levels of IgE antibodies, suggesting that a Th1 response was induced. In addition, we found that CD4+ T cells are the immunological effectors of DNA vaccination in this allergy model. Together, our results suggest the CryJ-LAMP Vaccine has a potential as an effective therapeutic for JRC induced allergy by skewing Th1/Th2 responses.